Small non-coding RNA profiling in breast cancer: plasma U6 snRNA, miR-451a and miR-548b-5p as novel diagnostic and prognostic biomarkers - Záveský, Luděk; Jandáková, Eva; Weinberger, Vít; Minář, Luboš; Hanzíková, Veronika; Dušková, Daniela; Faridová, Adéla; Turyna, Radovan; Slanař, Ondřej; Hořínek, Aleš; Kohoutová, Milada (Molecular biology reports, 2022)
BACKGROUND: Breast cancer is a leading cause of cancer-related death in women. Most cases are invasive ductal carcinomas of no special type (NST breast carcinomas). METHODS AND RESULTS: In this prospective, multicentric biomarker discovery study, we analyzed the expression of small non-coding RNAs (mainly microRNAs) in plasma by qPCR and evaluated their association with NST breast cancer. Large-scale expression profiling and subsequent validations have been performed in patient and control groups and compared with clinicopathological data. Small nuclear U6 snRNA, miR-548b-5p and miR-451a have been identified as candidate biomarkers. U6 snRNA was remarkably overexpressed in all the validations, miR-548b-5p levels were generally elevated and miR-451a expression was mostly downregulated in breast cancer groups. Combined U6 snRNA/miR-548b-5p signature demonstrated the best diagnostic performance based on the ROC curve analysis with AUC of 0.813, sensitivity 73.1% and specificity 82.6%. There was a trend towards increased expression of both miR-548b-5p and U6 snRNA in more advanced stages. Further, increased miR-548b-5p levels have been partially associated with higher grades, multifocality, Ki-67 positivity, and luminal B rather than luminal A samples. On the other hand, an association has been observed between high miR-451a expression and progesterone receptor positivity, lower grade, unifocal samples, Ki-67-negativity, luminal A rather than luminal B samples as well as improved progression-free survival and overall survival. CONCLUSIONS: Our results indicated that U6 snRNA and miR-548b-5p may have pro-oncogenic functions, while miR-451a may act as tumor suppressor in breast cancer.
Keywords: Biomarker; regulace genové exprese u nádorů; Humans; U6 snRNA; MicroRNAs; Biomarkers, Tumor; microRNA; Female; lidé; Biomarkers; RNA, Small Nuclear; nádorové biomarkery; RNA malá jaderná; Breast Neoplasms; biologické markery; ženské pohlaví; miR-451a; prognóza; miR-548b-5p; nádory prsu; mikro RNA; Breast cancer; prospektivní studie; Gene Expression Regulation, Neoplastic; Prognosis; Prospective Studies